Når lyrikken tager form. Boghistorie og nymaterialitet - Rasmussen, Krista Stinne Greve (Passage - Tidsskrift for litteratur og kritik, 2013)
Materialitetsproblematikken reflekteres ud fra en anden synsvinkel i Krista Stinne Greve Rasmussens artikel “Når lyrikken tager form. Boghistorie og nymaterialitet”, der er optaget af spørgsmålet om materialitet i trykte værker af Naja Maria Aidt, Mette Moestrup og Ursula Andkjær Olsen og viser, hvordan boghistorie kan anvendes som teoretisk afsæt for diskussionen af poesiens eksperimenter i relation til bogmediet. Krista Stinne Greve Rasmussen: “When Poetry Takes Shape. Book History and New Materiality” The article draws on the research field of Book History in an attempt to analyze new forms of materiality emerging in Danish poetry after 2000. The theoretical distinction between work, text, and document can help us to understand how poetical works increasingly articulate meaning in the material documents that present the text of the work. The development within new media creates a desire for that which Hans Ulrich Gumbrecht has termed “presence effects”. Analyzing works of Naja Maria Aidt, Mette Moestrup, and Ursula Andkjær Olsen the article demonstrates how Book History can be used as a theoretical point of departure for discussing experiments with materiality in poetry which are instances of a more general interest in the analogue world. Thus, there is a need for a greater understanding of the importance of materiality within literature.